Resolving the Paradox of Colon Cancer Through the Integration of Genetics, Immunology, and the Microbiota - Fidelle, Marine; Yonekura, Satoru; Picard, Marion; Cogdill, Alexandria; Hollebecque, Antoine; Roberti, Maria Paula; Zitvogel, Laurence (Frontiers in Immunology, 2020)
While colorectal cancers (CRC) are paradigmatic tumors invaded by effector memory lymphocytes, the mechanisms accounting for the relative resistance of MSI negative CRC to immunogenic cell death mediated by oxaliplatin and immune checkpoint inhibitors has remained an open conundrum (1). Here we propose the viewpoint where its microenvironmental contexture could be explained -at least in part- by macroenvironmental cues constituted by the complex interplay between the epithelial barrier, its microbial ecosystem, and the local immune system. Taken together this dynamic ménage-à-trois offers novel coordinated actors of the humoral and cellular immune responses actionable to restore sensitivity to immune checkpoint inhibition. Solving this paradox involves breaking tolerance to crypt stem cells by inducing the immunogenic apoptosis of ileal cells in the context of an ileal microbiome shifted towards immunogenic bacteria using cytotoxicants. This manoeuver results in the elicitation of a productive Tfh and B cell dialogue in mesenteric lymph nodes culminating in tumor-specific memory CD8+ T cell responses sparing the normal epithelium.